Lower range of molecular weight of xanthan gum inhibits cartilage matrix destruction via intrinsic bax-mitochondria cytochrome c-caspase pathway. (15th October 2018) - Shao, Xintian; Chen, Qixin; Dou, Xixi; Chen, Lei; Wu, Jixu; Zhang, Wei; Shao, Huarong; Ling, Peixue; Liu, Fei; Wang, Fengshan
Graphical abstract: Highlights: LRWXG inhibits cartilage matrix destruction in OA induced by ACLT. LRWXG regulates bcl-2, bax, caspase-9, caspase-3, and cyt-c in cartilage. LRWXG exerts anti-cartilage degradation effect via an intrinsic bax-mitochondria cytochrome c-caspase pathway. Abstract: We have previously reported an application of lower range of molecular weight of xanthan gum (LRWXG) for inhibiting cartilage matrix destruction and preventing mitochondrial damage in rabbit osteoarthritis (OA) model. However, whether LRWXG exerts its anti-OA activity through intrinsic bax-mitochondria cytochrome c-caspase signaling pathway in OA still requires further study. To address this problem, the OA model was induced by anterior cruciate ligament transection (ACLT) in rabbit and then treated with LRWXG. The results showed that LRWXG could inhibit the loss of collagen in cartilage matrix, protect trabecular bone in subchondral, decrease the apoptosis of chondrocytes, down-regulate the expressions of active caspase-9, active caspase-3 and bax, and up-regulate the expression of bcl-2. In addition, LRWXG could up-regulate the expression of cyt-c in mitochondria, while down-regulate the expression of cyt-c in cytoplasm. These findings show that LRWXG inhibits cartilage degradation via an intrinsic bax-mitochondria cytochrome c-caspase pathway in OA.